Dosimetric comparison in sparing normal tissue dosage by using auto-SBRT planning in oligo liver tumors - Zhang, Shu; Zhan, Weiyi; Zeng, Ni; Yang, Jiangping; Xiong, Maoqi; Liao, Wenjun; Chen, Nianyong; Xiao, Jianghong (Frontiers in Oncology, 2023)
Purpose： The study aimed to compare the dosimetric distribution of VMAT plans by increasing the number of half arcs in liver SBRT, and investigate the effect by using automatic plan software in plan optimization. Method: Thirty-one patients with oligo liver tumors were randomly selected. VMAT treatment plans with different numbers of coplanar half arcs were generated. Result: Adding arcs significantly increased the PTV, D2%, D50%, and CI, but sacrificed the plan homogeneity. It also decreased the maximum dose of normal tissues such as the stomach, duodenum, and spinal cord and reduced Dmean, D500cc, and D700cc for the liver.Nevertheless, the diminishing effect gradually decayed to three arcs. Meanwhile, the addition of arcs substantially extended the beam-on-time. Conclusion: In the context of SBRT for oligo liver tumor, increasing the number of coplanar half arcs will improve PTV conformity and offer better protection for OARs, albeit at the expense of increased treatment duration. Considering the trade-off between plan quality and the treatment efficiency, a three-arc plan may be more suitable for clinical implementation.